The constant ping: Examining the effects of after-hours work connectivity on employee turnover intention - Rasulova, Dilara; Tanova, Cem (Elsevier, 2025)
In today's technology-driven work environments, it is essential to understand how digital tools influence employee behavior and overall well-being. It is crucial to gain insights into these impacts, which is why this study aims to explore how employees perceive technology and how these perceptions influence their job engagement, burnout, and attitudes toward work connectivity after hours, resulting in employee turnover intentions. The study hypothesized that employees perceiving technology as a demand (e.g., requiring constant attention) would experience higher burnout, turnover intentions, and negative attitudes toward after-hours connectivity. Conversely, those perceiving technology as a resource (e.g., enabling flexibility) were expected to exhibit higher job engagement, positive attitudes toward after-hours connectivity, and lower burnout and turnover intentions. Drawing on the Job Demands-Resources theory, the research surveyed 250 government employees in Azerbaijan. Participants' perceptions of technology as demand and resource, job engagement, burnout, turnover intentions, and work connectivity after-hours attitude were assessed. Partial Least Squares Structural Equation Modeling analysis was used to test the research model. The results supported the hypotheses. Employees who perceived technology as a demand reported higher burnout, turnover intentions, and negative attitudes toward after-hours connectivity. In contrast, those who perceived technology as a resource exhibited higher job engagement, positive attitudes toward after-hours connectivity, and lower burnout and turnover intentions. These findings highlight the importance of considering technology's dual nature as both a demand and a resource in workplace design and management.
Keywords: Technology perception; Turnover intention; Work connectivity; After-hours attitude; Job engagement; Burnout